General practitioner referral of patients with lower gastrointestinal symptoms. - Springall, R G (1988)
Of 500 consecutive patients with symptoms of colorectal disease referred to a specialist hospital for outpatient assessment, 305 were studied. There was a low incidence of examination by the general practitioner; less than half the patients had a rectal examination and 31% had no examination at all. In cases where GPs made a diagnosis, this was correct in half, which both demonstrates the potential for dangerous misdiagnosis and confirms the fact that many anorectal conditions can be identified by the history alone. It is suggested that direct-access clinics in a colorectal unit would minimize delay in accurate diagnosis. The resource implications for such a system would be limited in terms of special investigations and additional clinic facilities.